2005
DOI: 10.1529/biophysj.104.053934
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Induced Conformational Change in the α7 Nicotinic Receptor Ligand Binding Domain

Abstract: Molecular dynamics simulations of a homology model of the ligand binding domain of the alpha7 nicotinic receptor are conducted with a range of bound ligands to induce different conformational states. Four simulations of 15 ns each are run with no ligand, antagonist d-tubocurarine (dTC), agonist acetylcholine (ACh), and agonist ACh with potentiator Ca(2+), to give insight into the conformations of the active and inactive states of the receptor and suggest the mechanism for conformational change. The main struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
61
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 56 publications
12
61
0
Order By: Relevance
“…7A, Table 1). These data are consistent with structural and molecular dynamic studies (1,3,4,(33)(34)(35) in the pLGIC family that indicate asymmetric subunit motions in the extracellular domain help power agonist-mediated gating. Recently, photochemical cleavage of the ␣-subunit GABA A R linker was shown to disrupt GABA activation (36).…”
Section: Discussionsupporting
confidence: 88%
“…7A, Table 1). These data are consistent with structural and molecular dynamic studies (1,3,4,(33)(34)(35) in the pLGIC family that indicate asymmetric subunit motions in the extracellular domain help power agonist-mediated gating. Recently, photochemical cleavage of the ␣-subunit GABA A R linker was shown to disrupt GABA activation (36).…”
Section: Discussionsupporting
confidence: 88%
“…It physically links loop C of the binding site to the membrane domain. Structural studies (Unwin et al, 2002;Celie et al, 2004) as well as molecular dynamic simulations (Henchman et al, 2005) reveal that agonist binding promotes movement of loop C inward to cap the binding site. We predict that this capping movement is propagated to the channel transmembrane domain by the pre-M1 region.…”
Section: Discussionmentioning
confidence: 99%
“…␣4 H195 was selected as a target because the equivalent histidine (␣4 H162 ) in the rat ␣4␤4 receptor was identified previously as a site involved in Zn 2ϩ potentiation (Hsiao et al, 2006) and also because this residue is located in loop F, which is a flexible loop (Szarecka et al, 2007) that may interact with the adjacent subunit in the non-ACh-binding interface. In the ␣4(ϩ)/␣4(Ϫ) interface of the (␣4) 3 (␤2) 2 receptor, ␣4(Ϫ) E92 in loop D and ␣4(ϩ) D217 and ␣4(ϩ) D218 in loop C, which is a very flexible loop as evident from x-ray crystal structures (Hansen et al, 2005) and molecular dynamics studies (Henchman et al, 2003(Henchman et al, , 2005, were identified that could form part of the binding site. In the ␤2(ϩ)/ ␣4(Ϫ) interface of the (␣4) 2 (␤2) 3 receptor, ␤2(ϩ) E224 was selected using this approach.…”
Section: ϩmentioning
confidence: 99%